Analytical model of microlens array system homogenizer. (December 2015) - Wang, Zexiong; Zhu, Guangzhi; Huang, Yan; Zhu, Xiao; Zhu, Changhong
Abstract: An analytical method is developed to optimally design the microlens array system homogenizer using ray tracing and non-paraxial approximation method. The relationship between the intensity distribution of beam and the height distribution of rays is built up to analyze the uniformity of focal spot for arbitrary incident beam. The analytical results show that the uniformity of focal spot shaping by mircolens array system has close relationship with incident beam intensity distribution, oblique incident angle, the number of microlens, and aberration of focal lens. The analytical approach and results are very useful for mircolens array system design and evaluation. Highlights: An analytical method is shown to optimally design the microlens array homogenizer. The model can analyze the uniformity of focal spot for arbitrary incident beam. The overlapping process of the beamlets will be shown clearly. The aberration of focal lens is a factor to affect the homogenization.